Selection Bias and the Underwriter Certification of the Largest Shareholders in Seasoned Equity Offerings - Lee, Chin Chong; Poon, Wai Ching; Sinnakkannu, Jothee (2017)
The largest shareholders of issuing firms in Hong Kong are eligible to underwrite rights issues and open offers. We hypothesize that the largest shareholders as underwriters who possess more information are better than investment banks in certifying firm value. Our analyses show that the largest shareholders self-select into their preferred issuing firms, and a selection bias in the choice of underwriters arises. After controlling for firm and issue characteristics and addressing the selection bias, our findings support our hypothesis. We also find that investment banks with greater access to information through prior underwriting relationship provide better certification than investment banks without such relationship.